The Role of the Smartphone in the Diagnosis of Vestibular Hypofunction: A Clinical Strategy for Teleconsultation during the COVID-19 Pandemic and Beyond - Barreto,Renato Gonzaga (2021)
Abstract Introduction Vestibular disorders (VDs) are highly prevalent in primary care. Although in general they comprise conditions that are not life-threatening, they are associated with significant functional and physical disability. However, the current Coronavirus disease 2019 (COVID-19) pandemic has imposed limitations on the standard treatment of benign conditions, including VDs. In this context, other resources may aid in the diagnosis and management of patients with VDs. It is well known that teleconsultation and teletreatment are both safe and effective alternatives to manage a variety of conditions, and we maintain that VDs should be among these. Objective To develop a preliminary model of clinical guidelines for the evaluation by teleconsultation of patients with suspected diagnosis of vestibular hypofunction during the COVID-19 pandemic and beyond. Methods A bibliographic review of the diagnostic feasibility in VDs by teleconsultation was carried out in the LILACS, SciELO, MEDLINE, and PubMed databases; books and specialized websites were also consulted. The legal, regulatory, and technical issues involving digital consultations were reviewed. Results We found 6 field studies published between 1990 and 2020 in which the efficiency of teleconsultations was observed in the contexts of epidemics and environmental disorders and disadvantageous geographical conditions. After reviewing them, we proposed a strategy to examine and address vestibular complaints related to vestibular hypofunction. Conclusion The creation of a digital vestibular management algorithm for the identification, counseling, initial intervention, monitoring and targeting of people with possible vestibular hypofunction seems to be feasible, and it will provide a reasonable alternative to in-person evaluations during the COVID-19 pandemic and beyond.